Digital Immigrants in Distance Education - Salazar-Márquez, Roberto (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2017)
The constant growth of methods of education that incorporate the Internet into teaching-learning processes has opened up a wide range of opportunities for students across the world to gain entry to undergraduate or graduate degree programs. However, if the enrolling student is a digital immigrant, the chances of success may be limited by the difficulty of using the Internet to communicate. This laid the groundwork for a qualitative study aimed at determining, from an ontological, epistemological, methodological, and instrumental approach, and from a teacher’s perspective, the main technical and communication challenges faced by digital immigrants as they follow an online higher-education study program.